PENGARUH KUALITAS PELAYANAN DAN NILAI PELAYANAN TERHADAP LOYALITAS NASABAH PADA BANK BPD JAWA TENGAH CABANG SEMARANG - Rusdarti, Rusdarti (JURNAL BISNIS STRATEGI, 2004)
The aim of this research is to know the influence of service quality and service value to the customer loyalty of Bank BPD Semarang. The research that is used are descriptive and verification with survey method, and taking sample technique which is simple random sampling and the proportional allocation. The sample size is 120 customer. The primer data are collected through documentation and questioner. The data analysis which is used path analysis. The result of this research shows that influence service quality and service value are influence the customer loyalty of Bank BPD Semarang. The influencing is shown by determination coefficient R2 = 0, 7726 or as equal as72,26%. The influence of each (variable) to the customer loyalty is about 50,47% and 21,80%. The Customers give a good appraisal performance to the Bank BPD Semarang.